2012
DOI: 10.1021/nn3015322
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Adsorbates on the Electronic Structure, Bond Strain, and Thermal Properties of an Alumina-Supported Pt Catalyst

Abstract: We describe the results of an X-ray absorption spectroscopy (XAS) study of adsorbate and temperature-dependent alterations of the atomic level structure of a prototypical, noble metal hydrogenation and reforming catalyst: ∼1.0 nm Pt clusters supported on gamma alumina (Pt/γ-Al(2)O(3)). This work demonstrates that the metal-metal (M-M) bonding in these small clusters is responsive to the presence of adsorbates, exhibiting pronounced coverage-dependent strains in the clusters' M-M bonding, with concomitant modif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 82 publications
9
73
0
8
Order By: Relevance
“…This study highlights that the charge exchange due to both metal-support and metal-adsorbate interactions plays an important role in mediating the structural dynamics of the supported nanoscale metal catalysts. Later, the same group studied the influence of adsorbates on the electronic structure, bond strain of the ~1.0 nm Pt/γ-Al 2 O 3 catalyst [52]. They demonstrated that the Pt−Pt bonding in these small clusters is responsive to the presence of adsorbates, exhibiting pronounced coverage-dependent strains, with concomitant modifications of their electronic structures.…”
Section: Science China Materialsmentioning
confidence: 99%
“…This study highlights that the charge exchange due to both metal-support and metal-adsorbate interactions plays an important role in mediating the structural dynamics of the supported nanoscale metal catalysts. Later, the same group studied the influence of adsorbates on the electronic structure, bond strain of the ~1.0 nm Pt/γ-Al 2 O 3 catalyst [52]. They demonstrated that the Pt−Pt bonding in these small clusters is responsive to the presence of adsorbates, exhibiting pronounced coverage-dependent strains, with concomitant modifications of their electronic structures.…”
Section: Science China Materialsmentioning
confidence: 99%
“…The reaction network in which they are involved is also very complex, due to the bifunctional nature of the system (metallic and acidic phase) and the various desired (isomerization, dehydrogenation, dehydrocyclization) and undesired (coking, hydrogenolysis, cracking) reactions. HRTEM [129][130][131][132][133] …”
Section: Acidity Of Oh Groups On Asa: On the Dominant Role Of The Stamentioning
confidence: 99%
“…This is important, because it is difficult to separate the effects of strong metal-support interactions and metal-ligand interactions on nanoparticle structure. [10][11][12][13] Second, DENs are sterically trapped within the dendrimers, and the Au surface does not interact strongly with the dendrimer host. 9 One consequence of this is that the Au surface is accessible to small molecules.…”
Section: Introductionmentioning
confidence: 99%